ANALISIS KETIMPANGAN PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI ACEH. - Dedi Saputra, Mohd. Nur Syechalad, Muhammad Nasir. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2015)
Abstract: This study aims to analyze how much inequality of education and what are the dominant factors that influence it and how much the influence on economic growth in province of Aceh. The data used in this research is secondary data obtained from the Central Bureau of Statistics, Bappeda Aceh and the Directorate General of Fiscal Balance - The Ministry of Finance of the Republic of Indonesia and the publication of previous research results which relevant to this study. Data analysis method used is the Gini index of Education, panel data regression analysis with pooled EGLS techniques. The results showed that the inequality of education in the province of Aceh is at a low level of inequality that is an average of 0.262. In the first regression model known that the independent variable levels of poverty and population impact positively and significantly to the educational inequality, while the independent variables education sector government expenditure has a negative and significant effect on educational inequality. In the second regression model known that the independent variables educational inequality has a negative and significant effect on economic growth in the province of Aceh. Results are expected to be a reference for the next course of a study and consideration in development planning in the province of Aceh. Keywords: Educational inequality, poverty, population, education sector government expenditure and gross regional domestic product (GRDP). Abstrak: Penelitian ini bertujuan untuk menganalis seberapa besar ketimpangan pendidikan dan faktor-faktor apa saja yang dominan mempengaruhinya serta seberapa besar pengaruhnya terhadap pertumbuhan ekonomi di Provinsi Aceh. Data-data yang digunakan dalam penelitian ini adalah data sekunder yang bersumber dari Badan Pusat Statistik, Bappeda Aceh dan Direktorat Jenderal Perimbangan Keuangan-Kementerian Keuangan Republik Indonesia serta publikasi hasil penelitian sebelumnya yang relevan dengan penelitian ini. Metode analisis data yang digunakan adalah Indeks Gini Pendidikan, analisis regresi data panel dengan teknik pooled EGLS. Hasil penelitian memperlihatkan bahwa ketimpangan pendidikan di Provinsi Aceh berada pada tingkat ketimpangan rendah yaitu rata-rata 0,262. Pada model regresi pertama diketahui bahwa variabel independen tingkat kemiskinan dan jumlah penduduk berpengaruh positif dan signifikan terhadap ketimpangan pendidikan, sedangkan variabel independen pengeluaran pemerintah sektor pendidikan berpengaruh negatif dan signifikan terhadap ketimpangan pendidikan. Pada model regresi kedua diketahui bahwa variabel independen ketimpangan pendidikan mempunyai pengaruh negatif dan signifikan terhadap pertumbuhan ekonomi di Provinsi Aceh. Hasil penelitian ini diharapkan dapat menjadi bahan rujukan bagi penelitian selanjutnya dan pertimbangan dalam perencanaan pembangunan di Provinsi Aceh. Kata Kunci: Ketimpangan Pendidikan, tingkat kemiskinan, jumlah penduduk, Pengeluaran Pemerintah Sektor Pendidikan dan Produk Domestik Regional Bruto (PDRB).